Neuropedagogical Approach in Indonesian Language Learning: Improving Elementary School Students' Motivation and Competence - Pebriana, Putri Hana; Nurhaswinda, Nurhaswinda; Nurmalina, Nurmalina (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
Indonesian language learning in elementary schools often struggles to enhance students’ motivation and competence, with conventional memorization-focused approaches proving ineffective. This study examined the effectiveness of a neuropedagogical approach, grounded in neuroscience and brain-based learning principles, on motivation and language competence. Using a quasi-experimental design, 70 fourth-grade students were assigned to experimental and control groups. The intervention applied multisensory activities, movement-integrated learning, emotional anchoring, and metacognitive reflection. Data from validated tests on reading, writing, speaking, listening, and motivation were analyzed using t-tests and n-gain scores. The experimental group achieved a high n-gain (0.76) compared to the control group (0.04), indicating significant improvement. Findings suggest integrating teacher training and curricula with brain-compatible strategies to foster intrinsic motivation and linguistic competence. This research highlights the potential of neuroscience-informed instruction to optimize language learning outcomes, with future studies recommended to explore long-term effects and broader implementation. Keywords: neuropedagogy, brain-based learning, learning motivation, indonesian language competence, neuroscience in education